The Interpretation of Anthropomorphic Verses in the View of Muhammad Husain Thabathabai - Nurul Khair; Siti Halimah; Siti Hadaynayah Salsabila (AJIS: Academic Journal of Islamic Studies, 2020)
This writing is library research on Muhammad Husain Thabathabai’s thought. It concerns about the anthropomorphist verses which is motivated by the interpretation of the Mujassimah to see that Allah SWT has a physical form in His existence by referring to anthropomorphic verses as the principle of argument. As a result, the existence of Allah as the Creator is the same as human existence. Besides the textual interpretation of anthropomorphic verses can be misunderstood, it's also known that rational view or liberal can cause misunderstanding in explaining about the meaning of divine word. In order to solve this problem, the writing is aimed to examine the interpretation of anthropomorphic verses to obtain the essence of existence of Allah SWT without relying on textual and rational understanding based on Muhammad Husain Thabathabai master piece, Al-Mīzan Tafsīr Al-Qur'an. By using descriptive-analytical method, this paper will get the conclusion that Muhammad Husain Thabathabai studied and examined the anthropomorphic verses using takwil approach as one of the esoteric interpretation methods which implies three terms, namely kinayah, siyaq or context of the verses, and Qur’an bil Qur’an. Based on these three terms, the authors use to question research that what are the implications of the interpretation of anthropomorphic verses in the view of the commentators and how Muhammad Husain Thabathabai's solution in solving the problematic interpretation of anthropomorphic verses. The results of this paper is to offer a new perspective in interpreting anthropomorphic verses, so that each individual can understand the essence and the degree of existence of Allah in his tawhid paradigm